Comparison of overall survival and unplanned hospital readmissions between partial and radical nephrectomy for cT1a and cT1b renal masses. Issue 12 (December 2018) - Chong, Julio T.; Paulucci, David; Lubin, Marc; Beksac, Alp Tuna; Gin, Greg; Sfakianos, John P.; Badani, Ketan K.
Background: The aim of the study was to compare overall survival (OS) and unplanned hospital readmissions (UHRs) within 30 days between partial nephrectomy (PN) and radical nephrectomy (RN) for clinically localized T1 renal tumors. Methods: The National Cancer Database was queried to identify 51, 018 patients who had undergone RN ( n = 23, 904; 46.9%) or PN ( n = 27, 114; 53.1%) for a cT1N0M0 renal mass from 2004 to 2013. OS and UHRs were compared using inverse probability of treatment weighted (IPTW)-adjusted Cox proportional hazards regression models. Results: For patients with a cT1a tumor, IPTW-adjusted analysis showed PN compared with RN was associated with improved OS (hazard ratio [HR] = 0.62; 95% confidence interval [CI] = 0.56, 0.67; p < 0.001) with a 5-year and 10-year IPTW-adjusted OS of 93.0% versus 88.2% and 78.1% versus 71.7%, respectively with no difference in UHR (odds ratio [OR] = 1.02; 95% CI = 0.90, 1.16; p = 0.727). For patients with a cT1b tumor, IPTW-adjusted analysis showed PN compared with RN to be associated with marginally improved OS (HR = 0.89; 95% CI = 0.82, 0.99; p = 0.025) with a 5-year and 10-year IPTW-adjusted OS of 85.3% versus 84.3% and 70.8% versus 63.6%, respectively, with more UHRs for PN (OR = 1.43; 95% CI = 1.19, 1.72; p < 0.001). Conclusions: PN compared with RN was associated with a significant survival benefit for patients with a cT1a renal mass and a modest survival benefit for patients with a cT1b renal mass. PN should be offered over RN when feasible despite a marginal increase in UHRs for PN of cT1b tumors. Randomized controlled trials are necessary to confirm these findings.